The Application of Cross-Cultural Management Theory in Implementing Personalized Employee Management: The Case of Huawei - Dai, Yuxuan (Transactions on Economics, Business and Management Research, 2024)
This article explores how cross-cultural management theory can effectively promote the implementation of personalized management for enterprise employees. In the context of global economic integration, cross-cultural management has become an important cornerstone of multinational business operations. By respecting and integrating different cultural backgrounds, not only can cultural conflicts be resolved, but also an inclusive corporate culture can be constructed, providing theoretical support for personalized management. Personalized management requires customizing management strategies based on employee characteristics, while cross-cultural management theory helps companies gain a deeper understanding of employee cultural backgrounds and needs, and develop precise management plans. Therefore, enterprises should actively adopt cross-cultural management theories and enhance their cross-cultural management capabilities to cope with the challenges of globalization. In order to effectively respond to the various challenges brought by globalization, enterprises must actively embrace cross-cultural management theories and strive to enhance their cross-cultural capabilities. Through this initiative, companies can deeply tap into and fully utilize the unique potential of their diverse workforce, creating an inclusive work environment where every employee feels respected and empowered. Such an environment can not only stimulate employees' enthusiasm and creativity, but also promote teamwork and innovation, ultimately laying a solid foundation for the sustained success and long-term development of the organization.